2021
DOI: 10.3390/antiox10091482
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Enhances the Mitochondrial Functionality of Brown Adipose Tissue in Obese—Diabetic Rats

Abstract: Developing novel drugs/targets remains a major effort toward controlling obesity-related type 2 diabetes (diabesity). Melatonin controls obesity and improves glucose homeostasis in rodents, mainly via the thermogenic effects of increasing the amount of brown adipose tissue (BAT) and increases in mitochondrial mass, amount of UCP1 protein, and thermogenic capacity. Importantly, mitochondria are widely known as a therapeutic target of melatonin; however, direct evidence of melatonin on the function of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Many regulatory effects of melatonin on cardiovascular, endocrine, reproductive, and immune systems are mediated via specific melatonin 1 (MT1) and MT2 membrane receptors [19,186]. Melatonin, by interacting with MT1 and MT2, has been found to limit weight gain [176,187,188]. Melatonin can inhibit adipogenic differentiation and together with vitamin D, exhibits a negative regulation of adipogenesis in adipose-derived stem cells (ADSCs).…”
Section: An Overview Of the Synthesis Metabolism And Function Of Mela...mentioning
confidence: 99%
“…Many regulatory effects of melatonin on cardiovascular, endocrine, reproductive, and immune systems are mediated via specific melatonin 1 (MT1) and MT2 membrane receptors [19,186]. Melatonin, by interacting with MT1 and MT2, has been found to limit weight gain [176,187,188]. Melatonin can inhibit adipogenic differentiation and together with vitamin D, exhibits a negative regulation of adipogenesis in adipose-derived stem cells (ADSCs).…”
Section: An Overview Of the Synthesis Metabolism And Function Of Mela...mentioning
confidence: 99%
“…On this basis, and since mitochondria are widely recognized as a therapeutic target for melatonin, it is reasonable to speculate that melatonin might protect against obesity-induced BAT dysfunction by improving the performance of mitochondrial respiratory and antioxidant functions. In support of this speculation, our previous study has shown that chronic oral administration of melatonin improved the functionality of mitochondria isolated from iBAT of the ZDF rats by increasing mitochondrial respiration and reducing mitochondrial oxidative/nitrosative stress and susceptibility to apoptosis [ 29 ]. Mitochondria are dynamic organelles that continuously divide and fuse, and the mitochondrial fission and fusion process plays a key role in providing a basis for mitochondrial functions, including respiration and oxidative stress balance [ 7 ].…”
Section: Discussionmentioning
confidence: 95%
“…Excessive mitochondrial fragmentation due to imbalanced mitochondrial dynamics has often been reciprocally linked to mitochondrial oxidative stress, which is critical for inducing cell death [ 5 , 7 ]. We have previously analysed the mitochondrial fractions of ZDF rats’ iBAT for superoxide dismutase (SOD) activity and nitrite level as markers of oxidative stress and mitochondrial permeability transition pore (mPTP) activity as a marker of apoptosis [ 29 ]. The results have shown reduced SOD activity associated with increased nitrite content and mPTP activity in untreated ZDF rats compared with their lean littermates [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of BAT in energy expenditure provides potential therapeutic prospects for counteracting obesity. In particular, the role of melatonin in stimulating BAT growth, enhancing BAT quality and activity, improving mitochondrial function and activities, and increasing UCP1 expression, as well as decreasing oxidative and nitrosative stress and susceptibility of adipocytes to apoptosis [ 85 ], make it an essential way to burn energy. Melatonin can regulate the physiology of BAT, which not only increases the recruitment of BAT cells but also enhances metabolic activity in mammals [ 14 ].…”
Section: Effect Of Melatonin On Obesitymentioning
confidence: 99%